Exchange Rate Pass-Through to Domestic Inflation in Ghana - Effah-Mensah, David; Essiam, Ebenezer (Business Economic, Communication, and Social Sciences Journal (BECOSS), 2024)
The current study estimates the exchange rate pass-through on domestic prices from January 2013 to December 2018, using a recursive vector autoregressive model (VAR). Applying Cholesky decomposition to the model, six variables were ordered as follows: oil prices, output gap, exchange rate, import prices, overall inflation and Treasury bill rate with an assumption that the identified shocks contemporaneously impact variables which are ordered after the shock without any contemporaneous feedback. We find evidence of incomplete exchange rate pass-through to domestic prices. Thus, domestic price changes by 9.6 percent in the first three months following an exchange rate shock and the shock dies out after a year with a total pass-through effect of 10.7 percent. We also find that, exchange rate effect is more pronounced for the imported prices than the overall inflation, suggesting some moderation of pass-through effect in domestic price dynamics.